Children’s (non-)participation in cyberbullying and emotional, behavioural problems - Raižienė, Saulė; Pakalniškienė, Vilmantė (Psichologija, 2019)
Technological changes are making the Internet more accessible and interactive. The opportunities offered by the Internet, Internet use (time, frequency, accessibility, social networks, activities, etc.), and threats are changing as well. Cyberbullying is identified as one of the main threats on the Internet that has the most serious consequences. Research has found that cyberbullying is the most frustrating Internet threat for children (Haddon & Livingstone, 2012). Considering that children do not live without the Internet, and that the opportunities and threats of the Internet change all the time, the impact on emotional and behavioural problems of children has not been fully explored. This study is part of the Lithuanian Science Council funded project “Children’s and adolescents’ Internet use in Lithuania: possibilities and risks tendencies in EU context” (No. S-MIP-17-1/LSS-250000-1087). It aims to compare emotional and behavioural problems of children who have been victims of different forms of bullying and/or bullied themselves. During the data collection in 2018, 1012 children aged 9 to 17 years were interviewed; 161 (15.9%) children reported being bullied over the last year (61.5% of them in cyber space), and 65 (6.4%) children bullied others over the last year (52.3% of them in cyber space). The results show that cyberbullying is more often related to traditional and other forms of bullying than it takes place separately. However, there is an overlap in bullying environments: children who have experienced traditional bullying, bully others in a traditional way; and children who have experienced cyberbullying, bully others in the cyber space. The results confirm that the experience of bullying is related to poor psychological functioning, but the most emotional and behavioural problems are experienced by those kids who participated in or experienced traditional bullying. According to the results of this study, the harm caused by a traditional bullying is greater than cyberbullying.